Nitrogen doped fluorescent carbon quantum dots for on-off-on detection of Hg2+ and glutathione in aqueous medium: Live cell imaging and IMPLICATION logic gate operation - Singh V.K.; Singh V.; Yadav P.K.; Chandra S.; Bano D.; Koch B.; Talat M.; Hasan S.H. (My University, 2025)
The present work describes the synthesis of N-CQDs via one step hydrothermal methods. The synthesized N-CQDs was fully characterized by TEM, P-XRD, FT-IR, XPS and Zeta sizer. It exhibited excitation independent emission behaviour with fluorescent quantum yield of 41% respect to quinine sulphate standard. The excellent optical properties of N-CQDs made it fluorescent probe for turn off detection of toxic heavy metal ion Hg2+ with good selectivity and sensitivity. The limit of detection was found to be 0.08 μM with correlation coefficient (R2 = 0.992). After addition of various reducing agent such as amino acid, EDTA and GSH in the quenched solution of N-CQDs + Hg2+, the fluorescence property was selectively recovered in the presence of GSH and hence the quenched solution further acts as selective turn on sensing of GSH up to lower limit of 2.0 μM with correlation coefficient (R2 = 0.996). The on-off-on sensing behaviour of N-CQDs was utilized for the implication of logic gate in absence and presence of Hg2+ and GSH to construct the molecular switches. The MTT assay of N-CQDs was performed on MCF-7 cancer cell line to check their applicability in biological system and the result showed negligible cytotoxicity and good permeability. The cell imaging on MCF-7 cells visualized in dichromic region (blue and green). Therefore, it could be smart material for sensing of heavy toxic metal as well as cell imaging application. © 2019 Elsevier B.V.